Urban Tourism: A Potential Tourism Attraction in Gorontalo City - Laxmiwaty Dai, Srilian; Asti Ayuningsih; Betly Taghulihi; Vidhia Agmareina Hirto; Wildayanti Limpas, Zulhajnie; Sunarti, Sri (Jurnal Internasional Riset Bisnis Pariwisata, 2023)
This research aims to examine the potential of urban tourism as a tourist attraction in Gorontalo City. This type of research is qualitative, with data collection methods through observation, interviews, literature studies, and documentation. In this research, interviews and observations were conducted as primary data, and literature studies and documentation were used as secondary data. The data in this study were analyzed descriptively and qualitatively. The results of this study show the potential of urban tourism in Gorntalo City, namely the governor's office, old town area, monument of Gorontalo national hero Nani Wartabone, Gorontalo culinary and culinary center, Gorontalo State University, Gorontalo Mall, Gorontalo central traditional market, city park, Taruna Remaja field, Dulohupa traditional house, Popa Eyato Museum, Tamendao Beach, Mufidah souvenir, Kerawang Shop, Baiturrahim Mosque and Hunto Mosque, Lahilote Swimming Pool and Sport Center, and Otanaha Fort. Furthermore, tourism-supporting components such as road availability and various modes of transportation, Djalaludin Airport, Gorontalo Port, and Dungingi Terminal There are also clinics, hospitals, and pharmacies; banks and money changers; mini markets; police stations to ensure the safety of tourists; and the Gorontalo City tourism office. The development of urban tourism attractions can be realized with the cooperation of all tourism stakeholders, both local government and the private sector.